ИНДУСТРИАЛИЗАЦИЯ - АЛДАҒЫ ОНЖЫЛДЫҚТА ҚАЗАҚСТАННЫҢ НЕГІЗГІ ДАМУ ФОРМУЛАСЫ (Journal of Philosophy, Culture and Political Science, 2018)
This article is devoted to analysis of the Industrialization as a main task of Kazakhstan Development.